Characterisation and Immunogenicity of Neisseria cinerea outer membrane vesicles displaying NadA, NHBA and fHbp from Neisseria meningitidis serogroup B - Manoharan, Shathviga; Farman, Theo A.; Piliou, Stavroula; Mastroeni, Pietro (Frontiers in Immunology, 2024)
More affordable and effective vaccines against bacterial meningitis caused by Neisseria meningitidis serogroup B are still required for global prevention. We have previously shown that modified outer membrane vesicles (mOMVs) from commensal Neisseria cinerea can be used as a platform to induce immune responses against meningococcal antigens. The aim of the present study was to use a combination of two genetically engineered mOMVs to express multiple antigens from N. meningitidis known to be involved in protective immunity to meningococcal meningitis (different variants of factor H binding protein (fHbp), Neisseria Heparin Binding Antigen (NHBA) and Neisseria Adhesin A (NadA)). Antigen expression in the mOMVs was confirmed by Western blotting; detoxification of the lipooligosaccharide (LOS) was confirmed by measuring human toll like receptor 4 (hTLR4) activation using in vitro cell assays. Mice immunised with a combination of two mOMVs expressing fHbp, NHBA and NadA produced antibodies to all the antigens. Furthermore, serum bactericidal activity (SBA) was induced by the immunisation, with mOMVs expressing NadA displaying high SBA titres against a nadA + MenB strain. The work highlights the potential of mOMVs from N. cinerea to induce functional immune responses against multiple antigens involved in the protective immune response to meningococcal disease.